2015
DOI: 10.1523/jneurosci.4000-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Input-Gain Control Produces Feature-Specific Surround Suppression

Abstract: In primary visual cortex (V1), neuronal responses are sensitive to context. For example, responses to stimuli presented within the receptive field (RF) center are often suppressed by stimuli within the RF surround, and this suppression tends to be strongest when the center and surround stimuli match. We sought to identify the mechanism that gives rise to these properties of surround modulation. To do so, we exploited the stability of implanted multielectrode arrays to record from neurons in V1 of alert monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…With this biphasic temporal profile, integration of the spiking response over short epochs yields facilitation compared to CRF stimulation alone ( Figure 6) as observed by Kapadia et al (2000). Integration of the response over longer stimulus durations leads to net measured suppression as the stronger, delayed suppressive component dominates over facilitation (Figure 6), as reported in many studies (Jones et al, 2001;Sceniak et al, 2001;Cavanaugh et al, 2002b;Webb et al, 2005;Hallum and Movshon, 2014;Trott and Born, 2015). We suggest that these differences in temporal integration among multiple eCRF components provide a parsimonious explanation for many previous conflicting reports about eCRF facilitation (and lack thereof).…”
Section: Relation To Previous Work On Ecrf Modulationsupporting
confidence: 54%
See 1 more Smart Citation
“…With this biphasic temporal profile, integration of the spiking response over short epochs yields facilitation compared to CRF stimulation alone ( Figure 6) as observed by Kapadia et al (2000). Integration of the response over longer stimulus durations leads to net measured suppression as the stronger, delayed suppressive component dominates over facilitation (Figure 6), as reported in many studies (Jones et al, 2001;Sceniak et al, 2001;Cavanaugh et al, 2002b;Webb et al, 2005;Hallum and Movshon, 2014;Trott and Born, 2015). We suggest that these differences in temporal integration among multiple eCRF components provide a parsimonious explanation for many previous conflicting reports about eCRF facilitation (and lack thereof).…”
Section: Relation To Previous Work On Ecrf Modulationsupporting
confidence: 54%
“…Studies of eCRF modulation that used large collinear annular gratings drifting for hundreds of milliseconds to many seconds typically reported finding strong eCRF collinear suppression but little or no collinear facilitation (Levitt and Lund, 1997;Hupe et al, 2001;Sceniak et al, 2001;Levitt and Lund, 2002;Cavanaugh et al, 2002a;Jones et al, 2002;Shushruth et al, 2012;Nassi et al, 2013;Henry et al, 2013;Trott and Born, 2015). Other studies, that used briefly presented spatially-localized stimuli flanking the CRF (Kapadia et al, 1995;Kapadia et al, 2000), reported a high prevalence of collinear facilitation.…”
Section: Relation To Previous Work On Ecrf Modulationmentioning
confidence: 99%
“…Similarly, the crowding effects we measured are not influenced by eye movements, since we administered paralytics to suppress these. Importantly, V1 spatial contextual effects are robust in awake animals, and have similar properties to the modulation observed under anesthesia 64,65 .…”
Section: Discussionmentioning
confidence: 60%
“…The experimental details have been described previously (Nassi et al, 2013;Trott and Born, 2015). Briefly, two male rhesus monkeys (Macaca mulatta), A and U, were implanted with a head post, a multi-electrode array (MEA) over the V1 operculum, and three custom made cryoloops (Lomber et al, 1999) into the lunate sulcus in an aseptic surgery under isoflurane anesthesia.…”
Section: Methods Summarymentioning
confidence: 99%